How Instagram can help city planners understand park usage and attractions: a case study of Klyde Warren Park - Kuneyl, Erin L. (Kansas State University, 2021)
Parks and open spaces are important for communities and the overall well-being of people. In dense urban areas, parks and green spaces provide a place where people can meet, exercise, and experience nature and open space that otherwise can be lost in downtown areas. Depending on the park and the specific amenities and qualities it has will influence the park’s usage. By analyzing social media posts that tag specific parks, planners are able to see parks through a new view. Unlike traditional research methods, such as interviews and surveys, social media is raw, unfiltered data. It is not filtered to try to tell the researcher what they want to hear. Analyzing Instagram posts brings us both raw data of words from the caption along with personal photographs. Researchers can understand what people are saying about these spaces, how they feel in a space, the events they are at, who they are with and why they are there. The photographs tell the researcher what people enjoy about the space, which amenities they like or the event that they want to remember. By using geolocation, we can narrow down a case study of Klyde Warren Park as a specific park location that people have tagged in downtown Dallas, Texas. This research demonstrates what social media, and more specifically Instagram analysis, can show to help inform planners in ways that people use and perceive parks. These findings help planners to understand how social media can help justify parks and understand park usage in dense urban environments and specifically Klyde Warren Park in downtown Dallas, Texas.
Keywords: Social media; Instagram; Klyde Warren Park; Qualitative